Pemerintahan, Demokrasi, dan Interpretasi Agama dalam Perspektif Abdul Karim Soroush - Mulyadi Mulyadi (Jurnal Filsafat "WISDOM", 2019)
Abdul Karim Soroush strives to offer solutions and restore religius-philosophy, government and democracy amid the wrestling of identity and discourse of thought in the Islamic world especially Iranian civilization and culture, from crisis of identity, psychological decline, to ontological dislocations that have obscured the authenticity of society’sexistential. This paper explains why Abdul Karim Soroush wants a new direction in theological and politicaldiscourse of Islam, especially in Iran, while supported by philosophical discourses.It employs the philosophy of science,in understanding human religiosity, thatrequires a new perspective in viewing reality, whether individual, social, or global. To counter the wave of authoritarianism, the article employsthe theory of depreciation and development of religious interpretation (the contraction and expansion of religious interpretation), by introducing three principlesof analysis namely: coherence or integration and correspondence, interpenetration, and evolution.